PERANCANGAN SARANA PEMBAWA UDANG HIDUP DENGAN METODE PEMINGSANAN UNTUK PEMANCING AIR ASIN - Peter Leonardo Wijaya; Kresno Soelasmono; Kumara Sadana Putra (Perpustakaan Universitas Surabaya, 2018)
Fishing as a hobby growing very vast, proved by number of companies that still develop products specifically targeted to support fishing activities. But there is problem that hasn’t been solved by producers about how to create a product as a container that can maintain fresh shrimp bait remain alive as long as possible during fishing, especially in salt water, can’t last long or die when they reached the fishing spot because they didn’t have appropriate carrier. Researcher has the idea of using a method of stunning (immotilization) to keep the shrimp always alive and fresh so it can be used a bait for fishing. The goal of this study is to design a product that is able to keep the state of carried shrimp bait fresh and alive during fishing, as well as convenient and comfortable carries for saltwater fisher.Data collection method used ini this study are In Depth Interview (IDI) with the subjects consist of experienced fisher, seller of fishing equipment, and shrimp seller around Surabaya. Observation that took shrimp ponds, role-playing as salt water fisher in Sepulu, Madura. And Focus Group Discussion (FGD) with interviewees consist of saltwater fisher community and fishers who own boat.The result of this study is design of a shrimp bait carrier that capable to maintain the bait to be able to survive for a long time, namely 24-36 hours.